Psoriasis and Respiratory Comorbidities: The Added Value of Fraction of Exhaled Nitric Oxide as a New Method to Detect, Evaluate, and Monitor Psoriatic Systemic Involvement and Therapeutic Efficacy. (23rd September 2018) - Santus, Pierachille; Rizzi, Maurizio; Radovanovic, Dejan; Airoldi, Andrea; Cristiano, Andrea; Conic, Rosalynn; Petrou, Stephen; Pigatto, Paolo Daniele Maria; Bragazzi, Nicola; Colombo, Delia; Goldust, Mohamad; Damiani, Giovanni
Abstract : Psoriasis is a chronic inflammatory systemic disease characterized by a wide range of comorbidities. Respiratory comorbidities are currently poorly characterized and with discordant results. The systemic state of inflammation caused by psoriasis acts de novo on respiratory tissues and amplifies preexisting inflammation from asthma or chronic obstructive pulmonary disease. Because the lungs act as a gas exchanger between the internal and external environment, the impact of chronic psoriasis inflammation may be easily assessed through the analysis of exhaled breath. The fraction of exhaled nitric oxide test (FeNO) is a potential noninvasive solution that can provide quantitative and qualitative indices of respiratory airway inflammation. FeNO is routinely used to screen and manage asthmatic patients. Recent pilot studies contain encouraging data that underscore its possible use with systemic inflammatory nonpulmonary diseases, such as psoriasis. FeNO may therefore be a useful tool to evaluate underestimated airway inflammation and at the same time globally evaluate the impact of systemically antipsoriatic therapies.